2020
DOI: 10.3389/fneur.2020.00909
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Guillain–Barré Syndrome: A Case Report and Review of Literature

Abstract: During the recent coronavirus disease 2019 (COVID-19) outbreak in Northern Italy, we observed a 57-year-old man developing acute motor-sensory axonal neuropathy, a variant of Guillain-Barré syndrome (GBS), 12 days after severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. Similarly to other bacterial and viral infections, dysregulation of the immune system due to post-infectious mechanisms, such as the molecular mimicry, could lead to an indirect damage of the peripheral nervous system relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 45 publications
(17 reference statements)
3
75
0
8
Order By: Relevance
“…After review of the 242 documents, we identified 430 patients with COVID-19 diagnosed based on PCR or serologic testing who had acute neurological symptoms prompting CSF testing [ [5] , [6] , [7] , [8] , [9] , [10] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After review of the 242 documents, we identified 430 patients with COVID-19 diagnosed based on PCR or serologic testing who had acute neurological symptoms prompting CSF testing [ [5] , [6] , [7] , [8] , [9] , [10] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , …”
Section: Resultsmentioning
confidence: 99%
“…CSF oligoclonal bands were tested in 114 patients who did not have a positive CSF SARS-CoV-2 PCR or positive CSF antibodies to SARS-CoV-2 (103 (90%) who had symptoms that localized to the CNS and 11 (10%) who had symptoms that localized to the PNS) [ 9 , 10 , 19 , 20 , 35 , 36 , 42 , 44 , 45 , 58 , 69 , 74 , 79 , 81 , 101 , 112 , 113 , 116 , 117 , 126 , 127 , 130 , 135 , 136 , 147 , 149 , 152 , 154 , 160 , [168] , [169] , [170] , [171] , 177 , 181 , 182 , [185] , [186] , [187] , [188] , 191 , 194 , 203 , 205 , 207 , 209 , 212 , 213 , 215 , 216 , 218 , 233 , 242 , 245 ]. Of these, 35 (31%) had matched CSF and serum bands [ 9 , 35 , 79 , 112 , 113 , 127 , 147 , 170 , 171 , …”
Section: Resultsmentioning
confidence: 99%
“… [ 402 ] ADEM F 51 Methylprednisolone I.V., IVIg [ 403 ] ANE F 59 High dose dexamethasone [ 404 ] Acute demyelination F 54 Glucocorticoids [ 405 ] Demyelinating lesions F 54 High dose dexamethasone Antiepileptic therapy [ 406 ] AMSAN F 70 IVIg [ 407 ] Guillain-Barré syndrome 7 M 57 IVIg [ 408 ] Guillain-Barré syndrome 1 M, 1 F 26 Plasma exchange, I.V. labetalol, IVIg [ 409 ] ANM and AMAN M 61 Methylprednisolone I.V., plasma exchange [ 410 ] Guillain-Barré syndrome M 57 IVIg [ 411 ] AIDP M 68 IVIg [ 412 ...…”
Section: Resultsmentioning
confidence: 99%
“…The countries where the studies were carried out were Italy ( 18 , 27 , 30 32 , 39 , 40 , 60 , 65 , 71 , 75 ), China ( 21 ), Iran ( 22 , 62 , 64 , 68 , 69 ), Morocco ( 38 ), Netherlands ( 41 ), Turkey ( 42 ), Canada ( 43 ), Austria ( 47 ), Switzerland ( 48 , 54 ), Spain ( 34 , 35 , 37 , 45 , 46 , 52 , 73 ), United States ( 19 , 33 , 49 , 59 , 66 ), France ( 36 , 44 , 50 ), UK ( 53 , 74 ), Germany ( 55 , 61 , 70 ), Tanzania ( 56 ), Brazil ( 57 ), Saudi Arabia ( 58 ), and Sudan ( 72 ). However, in a few of the studies and the patients, GBS symptoms preceded the symptoms of COVID-19 infection with a range of 7–10 days ( 27 , 28 , 44 ).…”
Section: Resultsmentioning
confidence: 99%